2009
DOI: 10.1105/tpc.109.071472
|View full text |Cite
|
Sign up to set email alerts
|

A Study of New Arabidopsis Chloroplast RNA Editing Mutants Reveals General Features of Editing Factors and Their Target Sites  

Abstract: RNA editing in higher plant organelles results in the conversion of specific cytidine residues to uridine residues in RNA. The recognition of a specific target C site by the editing machinery involves trans-acting factors that bind to the RNA upstream of the C to be edited. In the last few years, analysis of mutants affected in chloroplast biogenesis has identified several pentatricopeptide repeat (PPR) proteins from the PLS subfamily that are essential for the editing of particular RNA transcripts. We selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
195
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 175 publications
(203 citation statements)
references
References 61 publications
7
195
1
Order By: Relevance
“…A drop in clpP editing of 70% was found with a single amino acid change in CLB19 that led to a relatively minor decrease in affinity for the clpP ligand in vitro. Nevertheless, we have shown that binding of CLB19 to its targets is relatively robust to single changes in either the RNA sequences or the protein itself, consistent with the common ability of editing factors to recognize more than one editing site, often with quite divergent sequences (Hammani et al, 2009;Okuda and Shikanai, 2012). Overall, the results suggest that individual PPR motifs contribute to different extents to RNA recognition.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A drop in clpP editing of 70% was found with a single amino acid change in CLB19 that led to a relatively minor decrease in affinity for the clpP ligand in vitro. Nevertheless, we have shown that binding of CLB19 to its targets is relatively robust to single changes in either the RNA sequences or the protein itself, consistent with the common ability of editing factors to recognize more than one editing site, often with quite divergent sequences (Hammani et al, 2009;Okuda and Shikanai, 2012). Overall, the results suggest that individual PPR motifs contribute to different extents to RNA recognition.…”
Section: Discussionmentioning
confidence: 55%
“…The process requires PPR proteins to convey the necessary RNA specificity by binding in close proximity to the cytidine that will be edited (Okuda and Shikanai, 2012). Each PPR editing factor displays a high degree of specificity, directing editing at a very limited number of RNA target sites (Hammani et al, 2009;Okuda and Shikanai, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Using a reverse genetic screen of T-DNA mutants, Hammani et al (2009) searched for unedited transcripts of 34 known plastid RNAs that undergo editing, leading to the identification of six PPR proteins that together are responsible for editing nine sites in Arabidopsis plastid RNA. Interestingly, lack of editing in eight of these sites did not lead to an obvious difference in phenotype or growth habit between the mutant and wild-type plants grown under normal growth conditions.…”
Section: The Impactmentioning
confidence: 99%
“…Further analysis demonstrated that five of these PPR proteins edit multiple sites. Hammani et al (2009) examined the RNA sequences around the PPR target site to elucidate common RNA sequences. They were able of identify a 15-nucleotide stretch for four out of the five.…”
Section: The Impactmentioning
confidence: 99%
“…The editing extent of these sites is severely reduced to more than 90% in the orrm1 mutant (Table S1). In the Y2H analysis we also included RARE1 and OTP84, which are required for the editing of accD-794, ndhF-290, ndhB-1481, and psbZ-50, respectively (29,30). The editing extent of accD-794, ndhF-290, ndhB-1481, and psbZ-50 in the orrm1 mutant is identical to the wild-type plant (Table S1).…”
Section: Orrm1 Interacts With An Editing Recognition Trans-factor Thrmentioning
confidence: 99%